Bio-Ecological Research of Lily Leaf Beetle Lilioceris lilii Scopoli (Coleoptera: Chrysomelidae) in Bosnia and Herzegovina - Brzica, Mirjana (ENTOMOLOGIA HELLENICA, 2011)
In the present study some bio-ecological characteristics of Lilioceris lilii in Bosnia and Herzegovina are presented. The insect’s presence was confirmed in the majority of the researched locations in Bosnia and Herzegovina. The average body length of L. lilii was 7.64 mm (7.025 mm for the males while 8.106 mm for the females) and the average body width 3.75 mm. The average length of a fully developed larva was 6.36 mm, and the average width was 2.69 mm. In terms of the cocoon, the average length was 8.83 mm and its width was 5.82 mm. Duration of embryonic development under field conditions was 8.5 days in average. The average duration of larval development (4 instars) was 16 days and the pupal stage lasted approximately 18 days. Lilioceris lilii retreated into winter quiescence at the beginning of autumn, thereof completes one generation per year. In the area of Sarajevo in field conditions the number of the laid eggs per female was 130 in average. The insect undergoes its entire development at the Asian and Oriental species of lily, on all the above-ground parts of the plants. Lilium candidum lily species that was present in all home gardens in the observed areas was the major host of the L. lilii. Experimentation with Aloae vera proved that this species was not a host of L. lilii.